2003
DOI: 10.1523/jneurosci.23-12-04899.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Resurgent Sodium Current to High-Frequency Firing in Purkinje Neurons: An Experimental and Modeling Study

Abstract: Purkinje neurons generate high-frequency action potentials and express voltage-gated, tetrodotoxin-sensitive sodium channels with distinctive kinetics. Their sodium currents activate and inactivate during depolarization, as well as reactivate during repolarization from positive potentials, producing a "resurgent" current. This reopening of channels not only generates inward current after each action potential, but also permits rapid recovery from inactivation, leading to the hypothesis that resurgent current m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
388
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(419 citation statements)
references
References 61 publications
(75 reference statements)
30
388
1
Order By: Relevance
“…Partial blockade of Na V 1.1 and Na V 1.6 affects the amplitude of the action potential and the threshold for action potential generation, but selective deletion of Na V 1.1 channel did not affect these electrophysiological parameters. This finding suggests that Na V 1.6 current determines the threshold voltage for action potential generation and the amplitude of the action potential in these neurons, consistent with previous data indicating that Purkinje cells from mutant mice lacking Na V 1.6 channels were not capable of sustaining a constant rate of firing (Khaliq et al, 2003).…”
Section: Altered Firing During Partial Blockade Of Sodium Channelssupporting
confidence: 91%
See 1 more Smart Citation
“…Partial blockade of Na V 1.1 and Na V 1.6 affects the amplitude of the action potential and the threshold for action potential generation, but selective deletion of Na V 1.1 channel did not affect these electrophysiological parameters. This finding suggests that Na V 1.6 current determines the threshold voltage for action potential generation and the amplitude of the action potential in these neurons, consistent with previous data indicating that Purkinje cells from mutant mice lacking Na V 1.6 channels were not capable of sustaining a constant rate of firing (Khaliq et al, 2003).…”
Section: Altered Firing During Partial Blockade Of Sodium Channelssupporting
confidence: 91%
“…Persistent sodium current conducted by Na V 1.1 channels in Purkinje neurons is 1.4% of peak sodium current, similar to the lower end of the range of persistent sodium current recorded in transfected non-neuronal cells. Persistent and resurgent sodium currents are known to support the generation of rapid action potential firing in neurons (Raman and Bean, 1999a;Khaliq et al, 2003). Our finding that these two forms of sodium current are substantially reduced in Purkinje neurons of Na V 1.1 mutant mice provides a biophysical basis for the reduced capacity for repetitive action potential firing of these neurons.…”
Section: Discussionmentioning
confidence: 64%
“…Currents through these channels activate and deactivate rapidly, thereby limiting Na channel inactivation, facilitating Na channel recovery, and permitting depolarization soon after a spike (Gähwiler and Llano, 1989;Raman and Bean, 1999;Southan and Robertson, 2000;Womack and Khodakhah, 2002;Edgerton and Reinhart, 2003;Khaliq et al, 2003). The present results are suggestive of axonal K channels with similarly rapid gating kinetics.…”
Section: Evidence For Specializations Of Axonal Channelssupporting
confidence: 52%
“…For example, somatic voltage-gated Na channels have "resurgent" kinetic properties that promote rapid recovery from inactivation even at potentials that are only moderately hyperpolarized (Raman and Bean, 2001). This rapid recovery appears to be facilitated primarily by Na V 1.6 ␣ subunits associated with a putative protein that limits inactivation Grieco et al, 2002;Khaliq et al, 2003;Grieco and Raman, 2004). Although Na V 1.6 is the primary Na channel ␣ subunit in nodes in most parts of the nervous system Krzemien et al, 2000), it is unknown whether the nodal Purkinje Na channels share the distinctive kinetics of the somatic channels.…”
Section: Evidence For Specializations Of Axonal Channelsmentioning
confidence: 99%
“…Incorporating this difference in inactivation into a kinetic model of Purkinje sodium current demonstrated that the faster the rate of conventional inactivation, the less successfully the open-channel blocker competed with the inactivation gate, thereby reducing the amount of resurgent current (Khaliq et al, 2003).…”
Section: Introductionmentioning
confidence: 99%